Share

## What is the solution to the equation -4(2x+3) = 2x+6-(8x+2)? 0 x=-10 0 L 0 | 0

Question

Lost your password? Please enter your email address. You will receive a link and will create a new password via email.

Question

### For Mexican American infants born in Arizona in 1986 and 1987, the probability that a child’s gestational age is less than 37 weeks is 0.142

### need some help with this question : When driving to their family reunion, River’s mom drove 10 miles at a rate of x mph and then 25 mile

### In this lab you will use Excel to plot a distance x on the vertical axis and the inverse of mass m on the horizontal axis. That is, a plot o

### A bag contains 13 pieces of candy. In how many ways can five pieces be selected?

### A number is called a “decreasing number” if each digit in the number is less than the digit to its left. For example, 87420 is a decreasing

## Answers ( )

Answer:x = -8

Step-by-step explanation:-4(2x+3) = 2x+6-(8x+2)

Distribute

-8x-12= 2x+6-8x-2

Combine like terms

-8x-12 = -6x+4

Add 8x to each side

-8x-12 +8x = -6x+4+8x

-12 = 2x+4

Subtract 4 from each side

-12-4 = 2x+4-4

-16 = 2x

Divide each side by 2

-16/2 = 2x/2

-8 =x